Hillary Clinton is not Mitt Romney rich: Nouns modifying degree and dimension of adjectives - O'Hara, Charlie (Proceedings of Sinn und Bedeutung, 2019)
In loose English speech, speakers can be observed to use nouns to modify adjectives. This paper explores the four readings which this construction can attain, associated with four types of parameters typically associated with adjectives: degrees, judges, comparison classes, and dimensions. A formal analysis is put forth that derives all four phenomena by recentering pragmatic halos around the modifying noun.